A blame game and sticky labels: A qualitative study of osteopaths' experiences of managing patients with pain catastrophising. (March 2021) - Pelekanou, Reno; Thomson, Oliver P.
Abstract: Background: There is growing interest in how catastrophising negatively impacts patient outcomes, but little research on how osteopaths perceive and manage catastrophising within the realities of clinical practice. The aim of this study, therefore, was to explore osteopaths' experiences, understanding and attitudes towards the construct of pain catastrophising in patients and the strategies they employ to manage it. Methods: This qualitative study used in-depth semi-structured interviews with a sample of 9 UK registered osteopaths. The interviews were transcribed verbatim, and constructivist grounded theory was used as a framework for data collection, analysis and category generation. Results: Three categories were constructed from the data, each with three subcategories: 1) Category: Perceptions of catastrophising; sub-categories: Awareness of catastrophising, specific properties of catastrophising, a useful clinical construct. 2) Category: Approach to patient management; sub-categories: Catastrophising first aid, educating patients, the use of physical evidence. 3) Category: Osteopaths' pPerceived competence at managing catastrophising in patients. sub-categories: Understanding their professional role, level of clinical knowledge and skills, attitudes towards patients showing signs of catastrophising. Conclusion: Osteopaths found the construct of catastrophising clinically useful as they felt it possessed properties distinct from other negative psychosocial factors. Also, they felt relatively comfortable at managing the state in patients. However, the term catastrophising is problematic and can inadvertently result in stigmatising patients. The findings suggest that osteopaths should avoid labelling patients as 'catastrophisers', and instead seek to identify catastrophising aspects of the patient's presentation, contextualised within the patient's unique experience and narrative. This helps understand why patients are catastrophising, reduces practitioners' judgement towards them and helps to target the specific barriers to recovery. With a growing focus on psychosocial factors in musculoskeletal healthcare, there is perhaps a greater imperative to mitigate against psychosocial labels being inadvertently used to stigmatise patients.